Predictive properties of risk assessment instruments following self-harm. (June 2017) - Owens, David; Kelley, Rachael
Summary: This month's BJPsych publishes two important studies concerned with the use of risk assessment scales after self-harm, one a systematic review and the other a multicentre cohort study. We agree with the authors: that each study adds weight to the existing evidence that points towards avoiding the use of such scales in clinical practice.